Isolation and Characterization of Two Lytic Phages Efficient Against Phytopathogenic Bacteria From Pseudomonas and Xanthomonas Genera - Korniienko, Nataliia; Kharina, Alla; Zrelovs, Nikita; Jindřichová, Barbora; Moravec, Tomaš; Budzanivska, Iryna; Burketová, Lenka; Kalachova, Tetiana (Frontiers in Microbiology, 2022)
Pseudomonas syringae is a bacterial pathogen causing yield losses in various economically important plant species. At the same time, P. syringae pv. tomato (Pst) is one of the best-studied bacterial phytopathogens and a popular model organism. In this study, we report on the isolation of two phages from the market-bought pepper fruit showing symptoms of bacterial speck. These Pseudomonas phages were named Eir4 and Eisa9 and characterized using traditional microbiological methods and whole-genome sequencing followed by various bioinformatics approaches. Both of the isolated phages were capable only of the lytic life cycle and were efficient against several pathovars from Pseudomonas and Xanthomonas genera. Combining TEM virion morphology inspection and comparative genomics analyses, both of the phages were classified as members of the Autographiviridae family with a different degree of novelty within the known phage diversity. Eir4, but not Eisa9 phage application significantly decreased the propagation of Pst in the leaf tissues of Arabidopsis thaliana plants. The biological properties of Eir4 phage allow us to propose it as potential biocontrol agent for use in the prevention of Pst-associated bacterioses, and also as model organism for the future research of mechanisms of phage-host interactions in different plant systems.